The Effect of Games and Activities Based on Sher's Project on Fine and Gross Motor Skills in Slow-Paced Children - Sogand Ghasemzadeh; Nayereh Naghdi; Gholam.Ali Afrooz (University of Tehran, 2017)
The present study aimed at investigating the effect of games and activities based on Sher's Project on slow-paced children's fine and gross motor skills. The population of the study consisted of all slow-paced children aged between 6 and 8 in the city of Isfahan during the 2015-2016 academic year. The sample included 30 male slow-paced students selected by the convenience sampling method. Then, they were randomly divided into two groups: experimental (15 participants) and control (15 participants). To assess their fine and gross motor skills, the Bruininks-Oseretsky Test of Motor Proficiency (BOTMP) was employed. The experimental group was trained with games and activities based on Sher's Project during 24 one-hour sessions, and the control group received no training. To analyze the data, SPSS-21 and MANCOVA were used. The results indicated that games and activities based on Sher's Project affected gross motor skills (P=0.001) and fine motor skills (P=0.001) in slow-paced children. Accordingly, it can be inferred that games and activities based on Sher's Project are appropriate to improve fine and gross motor skills in slow-paced children and can be used in educational and rehabilitation centers.